EXTRA ROLE BEHAVIOR OF THE APPARATUS IN THE IMPLEMENTATION OF THE PERATURAN GUBERNUR PROVINSI DKI JAKARTA NOMOR 115 TAHUN 2016 CONCERNING KETUK PINTU LAYANI DENGAN HATI PROGRAM - Diraisnu Gozali; Erna Setijaningrum (DIA: Jurnal Administrasi Publik, 2023)
This article aims to describe the extra role behavior carried out by the apparatus in implementing Ketuk Pintu Layani Dengan Hati Program and the factors that influence it. As an effort to reduce the rate of disease transmission in DKI Jakarta, the DKI Jakarta Provincial Government issued DKI Jakarta Governor Regulation Number 115 of 2016 concerning Ketuk Pintu Layani Dengan Hati Program. The scope of this program includes promotive, preventive, and curative with a door-to-door service mechanism. In implementing the program, it involves Public health center officers and health cadres in the DKI Jakarta province. To explain extra role behavior, Organ's theory of Organizational Citizenship Behavior is used. The research method used is descriptive qualitative. Data was collected by means of interviews, observations, and documents. The technique of determining informants is through purposive sampling, by determining key informants who develop into snowballs. The results of this study indicate that in the implementation of the Ketuk Pintu Layani Dengan Hati Program in DKI Jakarta Province, the apparatus must apply extra role behavior. Doctors, nurses, midwives, and health cadres must carry out their duties beyond their main duties. This can be identified from the dimensions of altruism, sportsmanship, civic virtue, conscientiousness, and participation. While the factors that influence the extra role behavior of the apparatus are cultural factors and organizational climate and job satisfaction factors.